IL-13 Signaling in Liver Fibrogenesis - Liu, Yan; Munker, Stefan; Müllenbach, Roman; Weng, Honglei (Frontiers in Immunology, 2012)
Liver fibrosis is the final common pathway of chronic liver diseases irrespective of etiology. However, etiology deeply impacts progression and characteristics of liver fibrogenesis. IL-13 is the dominant pro-fibrotic cytokine in Schistosomiasis associated liver fibrogenesis. In vitro, IL-13 directly induces expression of fibrosis associated genes, e.g. collagens or connective tissue growth factor, by hepatic stellate cells. Recently, potential effects of IL-13 in non-Schistosomiasis associated liver fibrosis start to be uncovered. This review summarizes the potential roles of IL-13 in chronic liver disease of different etiologies, and the downstream events mediating IL-13 signaling in liver fibrogenesis.